Toxicity of metal-based nanoparticles: Challenges in the nano era - Zhang, Naiding; Xiong, Guiya; Liu, Zhenjie (Frontiers in Bioengineering and Biotechnology, 2022)
With the rapid progress of nanotechnology, various nanoparticles have been applicated in our daily life. However, the unique physicochemical properties of nanoparticles confer not only promising biological effects but also pose unexpected toxic threats to the human body at the same time. For the safer application of nanoparticles in humans, we should comprehensively understand nanoparticle toxicity. In this review, we summarize our current knowledge about nanoparticles, including the physicochemical properties affecting their toxicity, mechanisms of their toxicity, their toxicological assessment, and the potential strategies to mitigate their toxicity. Hopefully, in the near future, through the convergence of related disciplines, the development of nanotoxicity research will be significantly promoted, thereby making the application of nanoparticles in humans much safer.